The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1158/1078-0432.ccr-19-0994
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib inMET-Deregulated orROS1-Rearranged Pretreated Non–Small Cell Lung Cancer (METROS): A Phase II, Prospective, Multicenter, Two-Arms Trial

Abstract: Purpose: MET-deregulated NSCLC represents an urgent clinical need because of unfavorable prognosis and lack of specific therapies. Although recent studies have suggested a potential role for crizotinib in patients harboring MET amplification or exon 14 mutations, no conclusive data are currently available. This study aimed at investigating activity of crizotinib in patients harboring MET or ROS1 alterations.Patients and Methods: Patients with pretreated advanced NSCLC and evidence of ROS1 rearrangements (cohor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
121
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(134 citation statements)
references
References 35 publications
10
121
1
2
Order By: Relevance
“…35 Similarly, the METROS phase II trial also showed a very high ORR of 65% and median PFS of 22.8 (95% CI 15.2--30.3 months with crizotinib therapy among 26 patients with ROS1-rearranged pretreated NSCLC. 36 Two studies from India have reported a good response to crizotinib therapy. 19,20 In one study, crizotinib therapy achieved an ORR of 93.8%, with 1-and 2-year OS of 72% and 54%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…35 Similarly, the METROS phase II trial also showed a very high ORR of 65% and median PFS of 22.8 (95% CI 15.2--30.3 months with crizotinib therapy among 26 patients with ROS1-rearranged pretreated NSCLC. 36 Two studies from India have reported a good response to crizotinib therapy. 19,20 In one study, crizotinib therapy achieved an ORR of 93.8%, with 1-and 2-year OS of 72% and 54%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this has led to drugs, which inhibit multiple targets being licensed for indications that are relevant to one target and not to the other. For example, sorafenib is licensed in renal cancer for its VEGFR inhibitory activity but not in melanoma for its RAF inhibitory activity (38,39), and crizotinib has been licensed in lung cancer for its ALK inhibitory activity but not as an MET inhibitor (40,41). AT13148 inhibited multiple AGC kinases and was found to cause cell death and apoptosis when compared with more selective AKT inhibitors in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The juxtamembrane domain is encoded in part by MET exon 14 and contains several important regulatory elements, including the c-Cbl binding site, which contributed to the degradation of MET protein (41). MET X1010 splice alteration is known to be oncogenic, and LUAD patients harboring MET exon 14 alterations, such as MET X1010_splice, can be treated with the NCCN-compendium listed drug crizotinib (32,33). However, several recent reports have shown that many patients receiving these MET small molecule inhibitors showed progression, and further studies to understand the resistance mechanisms are required (42).…”
Section: Discussionmentioning
confidence: 99%